Urban ecological design : A process for regenerative places - Palazzo, Danilo (Island Press/Center for Resource Economics, 2012)
Urban Ecological Design presents an interdisciplinary method of transforming urban spaces that considers issues of ecology and sustainability alongside urban form. Rather than offer a prescriptive approach, the authors describe a "process model" that has been developed and tested over time. They illustrate the different stages of the design process using theories, techniques, images, and case studies that will inform any urban design project.